Analysis of Factors Forming Attitude towards Brand and Repurchase Intention by Using Brand Ambassadors on the Shopee Online Shopping Platform - Muhammad Luthfi Haiban; Santi Rimadias (Indonesia Banking School, 2023)
The development of online shopping is increasing which is marked by the growth of various kinds of e-commerce, one of which is Shopee. The purpose of this study is to examine and analyze the factors that shape Attitude towards Brand and Repurchase Intention by using Blackpink as a Brand Ambassador on the Shopee online shopping platform. Respondents in this study were consumers who had made a purchase transaction on the Shopee online shopping platform, which amounted to 135 respondents and the data was processed using Smart PLS software. The results of the study explain that Brand Image and Brand Credibility have a positive effect on Attitude towards Brand. Furthermore, there is a positive effect of Endorser Likeability on Attitude towards Brand and there is a positive effect of Attitude towards Brand on Repurchase Intention. Meanwhile, it was found that Endorser Credibility had no effect on Attitude towards Brand, and Brand Image, Brand Credibility, Endorser Credibility, Endorser Likeability had no effect on Repurchase Intention.